2021
DOI: 10.1016/j.it.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of Interleukin 10 in COVID-19 Pathogenesis

Abstract: A unique feature of the cytokine storm in COVID-19 is the dramatic elevation of IL-10. Its significance was thought as a negative-feedback mechanism for suppressing inflammation. However, several lines of clinical evidence suggest that dramatic early pro-inflammatory IL-10 elevation might play a pathological role in COVID-19 severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
285
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(322 citation statements)
references
References 15 publications
(46 reference statements)
30
285
3
4
Order By: Relevance
“…Administration of recombinant IL-10 caused elevation in levels of LPS-induced IFN-γ release in healthy volunteers [ 65 ], and levels of phytohaemagglutinin-induced IFN-γ in moderate Crohn’s Disease patients [ 66 ]. In view of its pro-inflammatory nature, Lu et al [ 67 ] have proposed a two-stage participatory role of IL-10 in COVID-19 disease progression. At the initiation of viral infection, IL-10 acts as a countermeasure to the pro-inflammatory modulators in a negative feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of recombinant IL-10 caused elevation in levels of LPS-induced IFN-γ release in healthy volunteers [ 65 ], and levels of phytohaemagglutinin-induced IFN-γ in moderate Crohn’s Disease patients [ 66 ]. In view of its pro-inflammatory nature, Lu et al [ 67 ] have proposed a two-stage participatory role of IL-10 in COVID-19 disease progression. At the initiation of viral infection, IL-10 acts as a countermeasure to the pro-inflammatory modulators in a negative feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, IL-10 has been shown to partially exert its anti-inflammatory activities by inhibiting the transcription of IFN-inducible genes through suppression of STAT1 phosphorylation [37], suggesting that early production of IL-10 could mediate delayed inflammatory signalling, which has been suggested to contribute to a subsequent excessive inflammatory response [35]. Notably, chronic upregulation of IL-10 has already been shown to contribute to the progression of inflammatory diseases [38] [39,40], as it might occur in later/severe stages of COVID-19. In support of this hypothesis, IL-10-producing myeloid-derived suppressor cells (MDSCs) are massively and early expanded (at their first evaluation, 3/5-days after admission) in severe COVID-19 patients, which, at later recovery times, show both slow MDSC decline and concomitant inflam-matory cytokine storm [41], ultimately indicating that inflammatory response may be elicited subsequently to immunosuppression (an immunosuppressive response followed by a counter-inflammatory process, finally leading to a form of "immune paralysis") (see Figure 1).…”
Section: Crucial Role Of Il-10 In Covid-19 Pathogenesismentioning
confidence: 99%
“…In this regard, administration of IL-10 in humans has been shown to enhance peripheral production of IP-10 and undesired pro-inflammatory effects [40], suggesting that IP-10 secretion is downstream IL-10. Finally, several lines of evidence suggest that the early and dramatic IL-10 elevation upon SARS-CoV-2 infection might play a detrimental pathological role in critically COVID-19 patients and IL-10 has also been proposed as a potential target for reducing COVID-19 mortality [3,39]. Indeed, IL-10 was strongly downregulated (p < 0.001, even more than IL-6, p < 0.01) in SARS-CoV-2infected hamsters treated with ranitidine bismuth citrate [10], further suggesting its crucial role in disease pathogenesis.…”
Section: Crucial Role Of Il-10 In Covid-19 Pathogenesismentioning
confidence: 99%
“…The cytokine storm landscape of COVID-19 patients was further demonstrated in a retrospective study showing higher concentrations of IL-2, IL-7, IL-10, G-CSF, C-X-C motif chemokine ligand (CXCL)-10, C-C motif chemokine ligand (CCL)-2, CCL-3, and TNF- α in the plasma of severe COVID-19 patients ( Huang et al, 2020 ; Lu et al, 2020 ). Similarly, previous studies also showed higher levels of some cytokines, such as IFN- γ , TGF- β , IL-1, IL-6, IL-8, and IL-12 in the serum of SARS and MERS patients, highlighting the cytokine storm role in the pathogenesis of severe coronaviruses infection ( Channappanavar and Perlman, 2017 ).…”
Section: Cytokine Storm In Covid-19mentioning
confidence: 90%